Environmental Injustice in the water Sector in Sri Lanka - Tennakoon, Samudri Dilmika Ronali; Mahees , M. T. M. (Technium Social Sciences Journal, 2021)
An increase in water requirements with climate change has become a burning issue in South Asia. Over 2 billion people experience high water stress at present. According to UN predictions, by 2030 from 24 to 700 million people will be displaced by intense water scarcity experiencing a shortage of access to sufficient quantities of water for human and environmental use. The hydraulic empires of Sri Lanka in the past in Orient societies had been concerned about water conservation and storage to use during water shortages and to develop irrigation systems. They enforced their power and bureaucracy extensively to develop the waterworks systems with great skills and technology and water management model. At present, free-flowing water has become a profit-generating mechanism, creating injustice and inequalities in the water sector in Sri Lanka. Due to Inequality in water allocation, distribution, and access to water resources have made social inequalities making opportunities for the affluent class to gain, waste, and exploit water resources while have-nots lose and struggle leading them to poverty and social breakdown. With globalization and modernization, depletion of natural resources brought devastating impacts on marginalized communities making conflicts between human and environmental resources. With the human interaction of the global biosphere, marginalized communities who are least responsible for the pollution and degradation, undergo environmental injustice by experiencing the global environmental consequences as a result of rapid industrialization and resource exploitation at global and local levels. The main objective of the study was to explore the discourse of environmental justice in the water sector in Sri Lanka. The study is based on both qualitative and quantitative data. Content analysis of the relevant literature, informal discussions, and observations were carried out. Environmental injustice occurs when unequal societies place most of a load of environmental damage caused by development on low-income populations, discriminated social groups, disadvantaged communities, traditional ethnic communities, working-class, marginalized, and vulnerable populations. Also, Environmental injustice makes developing countries suffer from limited environmental resources creating inequalities in natural resources between countries and societies. Environmental inequality and political economy are interrelated and a global phenomenon. Trade, transfers of wastes, trade-in toxic waste, and climate change expand the injustice where value is accumulated only by one party while deepening and distributing global environmental risks to the other. As a response to these environmental inequalities, injustices, and racism, adequate attention was given beyond national boundaries on sustainable resource conservation to eradicate socioeconomic environmental inequalities. Communities live in hazardous and unfavorable conditions based on race/ethnicity, social class, gender, age, and location seem to be affected by environmental burdens and, in contrast, mainstream environmentalists began to focus on sustainability and conservation, which raises issues on the fairness of humans’ treatment of the environment.